Novel SNP markers and other stress-related genomic regions associated with nitrogen use efficiency in cassava - Mbe, Joseph Okpani; Dzidzienyo, Daniel Kwadjo; Abah, Simon Peter; Njoku, Damian Ndubuisi; Onyeka, Joseph; Tongoona, Pangirayi; Egesi, Chiedozie (Frontiers in Plant Science, 2024)
Cassava productivity is constrained by low soil nitrogen, which is predominant in most cassavagrowing regions in the tropics and subtropical agro-ecologies. Improving cassava's low nitrogen tolerance has become a very important breeding objective. The current study aimed at developing cassava varieties with improved nitrogen use efficiency through the identification of genomic regions and candidate genes linked with nitrogen use efficiency in cassava. A genomewide association study (GWAS) was carried out using the Genome Association and Prediction Integrated Tool (GAPIT). A panel of 265 diverse cassava genotypes were phenotyped for ten physiological and agronomic traits under optimum and low nitrogen regimes. Whole-genome genotyping for these cassava clones was performed using the Diversity Arrays Technology (DArTseq) sequencing platform. A total of 68,814 single nucleotide polymorphisms (SNPs) were identified, spreading across the entire 18 chromosomes of the cassava genome, of which 52 SNPs at various densities were identified to have associations with nitrogen use efficiency in cassava and other yield-related traits. The putative genes identified through GWAS, especially those with significant associated SNP markers for NUE and related traits, have the potential, if deployed appropriately, to develop cassava varieties with improved nitrogen use efficiency, which would translate to a reduction in the economic and environmental cost of cassava production.